Human trafficking in Malaysia - Ab Hamid, Zuraini (IIUM Press, International Islamic University Malaysia, 2017)
Human trafficking is a transnational organised crime which has threatened all regions around the world including Malaysia. Currently there are no books in the market that addresses the prevalent occurrence of human trafficking in Malaysia. Most of the materials such as articles, journals, books and writings are from the international market, written by foreign researchers and can only be gathered from the internet. Nevertheless, these works are very much constrained within the laws and practice in the selected countries which in certain cases are not suitable to be adopted elsewhere, especially in Malaysia due to differences in culture, geography, laws or policies. None of the writers managed to disclose the extent of human trafficking issues in a state government. Their argument also lacks concrete evidence, including absence of reliable data and statistics.